Developing countries and the WTO negotiations: essay from IFPRI's 2002-2003 Annual Report - Díaz-Bonilla, Eugenio; Gulati, Ashok (International Food Policy Research Institute, 2003)
A dynamic agricultural sector is crucial for economic growth, poverty alleviation, and food security in developing countries. Although primary agricultural activities are declining over time as a share of the economy, they still represent about one-fourth of total economic activity and 60 percent of total employment in low-income developing countries. Primary and processed food products account for about 20 percent of these countries' merchandise trade. Moreover, of the 1.2 billion people living on less than US$1 a day, about 75 percent live and work in rural areas in developing countries.....In spite of its importance, agricultural growth in developing countries has been hampered over the years by a series of factors.